Tradisi Luru Duit di Indramayu - Sulistyo Budiarto; Koentjoro Koentjoro (Universitas Andalas, 2017)
Child prostitution in Indramayu has been done for generations and has been formed into a tradition. Prostitution in Indramayu known as the luru duit meaning work for money or livelihood. Referring to the meaning of luru duit, shows that prostitution has been accepted as a form of work, similar to another forms of work. This study aims to identify the factors that influence luru duit phenomenon. Research uses the Etno-phenomenological method. Collecting data through interviews, observation and documents. The result shows luru duit is a planned behavior, it can be seen from three factors interacting. Internal factors include a positive attitude on materialism, the motivation to follow the views of others, the perception of ease on doing luru duit. External factors include micro and macro level. At the micro level includes the ability to access opportunities, namely the lack of jobs and poor education. At the macro level includes social situations, for example, early marriage and divorce as well as the situation of a long history of forming Bong village as the sender area of women for prostitution. The phenomenon of luru duit facilitates by the presence of the figure of the channel. Chanel as a liaison has amode in two ways, namely using violence method, coercion and fraud. The second way is to utilize the victim and the victim's parents desire for a better life in a way to seduce with money.